Transforming Indonesia's Teaching Force : Executive Summary - World Bank (World Bank, 2012)
The report on the transforming Indonesia's teaching force is divided in two volumes. The executive summary is the first volume of a two-volume comprehensive report on teacher management in Indonesia. This volume summarizes the key findings of the detailed technical analysis in volume two, but with much greater focus on the key areas where policy reforms will likely generate a large impact in Indonesia. While volume two is aimed at public policy researchers and technical staff of the Government of Indonesia, this shorter volume provides policy makers and the general public a condensed version of the larger report's analysis, results, and recommended policy reforms for developing a better teaching force in Indonesia. This report not only can assist the government in setting up a future reform agenda, but also add value to ongoing educational reform in Indonesia, in terms of improving the effectiveness of reform and ensuring its institutional and fiscal sustainability.